2016
DOI: 10.1364/oe.24.003774
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast acousto-optic imaging with ultrasonic plane waves

Abstract: Due to multiple light scattering inside biological tissues, deep non-invasive optical medical imaging is very challenging. Acousto-optic imaging is a technique coupling ultrasound and light that allows recovering optical contrast at depths of few centimeters with a millimeter resolution. Recent advances in acousto-optic imaging are using short focused ultrasound pulses often averaged over several hundred or thousand pulses. As the pulsing rate of commercial probes is limited to about few ultrasound cycles ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…This is because the dimension of the AOTM with L ultrasound foci would result in a matrix with L × M × N SLM elements. The size of the matrix, and the acquisition time, may be lowered by replacing the focused ultrasound beams with ultrasonic plane waves, or other parallelized measurements, which can be digitally coherently combined to synthetize various ultrasonic foci in 3D 59,60 . The AOTM could also be extended to non-monochromatic optical illumination, providing spectral, and temporal information on the medium’s response, This could be realized by using ultrashort optical pulses 16 , or spectrally tunable sources 61 , but would results in even higher dimensionality of the AOTM.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the dimension of the AOTM with L ultrasound foci would result in a matrix with L × M × N SLM elements. The size of the matrix, and the acquisition time, may be lowered by replacing the focused ultrasound beams with ultrasonic plane waves, or other parallelized measurements, which can be digitally coherently combined to synthetize various ultrasonic foci in 3D 59,60 . The AOTM could also be extended to non-monochromatic optical illumination, providing spectral, and temporal information on the medium’s response, This could be realized by using ultrashort optical pulses 16 , or spectrally tunable sources 61 , but would results in even higher dimensionality of the AOTM.…”
Section: Discussionmentioning
confidence: 99%
“…By using a random model for the movement of the blood cells, we have shown that an SVD approach can separate the blood signal from the clutter signal. Our model and results open a door for a mathematical and numerical framework for realizing super-resolution in dynamic optical coherence tomography [12], in ultrafast ultrasound imaging by tracking microbubbles [9], as well as in acousto-optic imaging based on the use of ultrasound plane waves instead of focused ones, which allows to increase the imaging rate drastically [13]. These three modalities are under investigation and their mathematical and numerical modeling will be the subject of forthcoming papers.…”
Section: Discussionmentioning
confidence: 93%
“…The acquisition time can be shortened by orders of magnitude using faster detection approaches, such as lock-in camera detection [27], and fast cameras [28]. Another approach for improved acquisition time is using an ultra-fast plane-wave AOT approach [25], based on nonlinear crystals.…”
Section: Discussionmentioning
confidence: 99%